The influence of a porous sealing insert on forces and deformations occurring in a threaded connection of a polymer packaging - Bieliński, M.; Czyżewski, P. (Polimery, 2014)
This article presents results of the research on the influence of porous sealing insert on the selected utility indices of a threaded connection in a polymer packaging. The research was divided into two phases. The first phase concerned the screwing of the threaded connection (between parts made of two types of high density polyethylene materials) in a lab stand for testing threaded connections "Vortex-i” by Mecmesin®. In this phase the influence of the thickness of the porous sealing insert on the tightening torque and the screwing angle was determined. The second phase concerned deformation (compression) of the porous sealing insert in the threaded connection with the help of a stress-strain machine, Zwick/Roell Z030. The research allowed to determine the range of deformations that occur in a sealing element (i.e. porous insert) depending on its thickness, as well as in a polymer cap itself in the function of a tightening torque and a screwing angle.